Protein expression in C57BL/6J mice during spatial learning in the Morris water maze - Seyedeh Zeinab Taheri Mirani (2012)
Learning and memory are two important physiological and biochemical processes that enable a living organism to adapt to the challenging environment. During learning there are changes in behaviour based on experience which consequently can lead to changes in memory. The mechanism of laying down learning and memory involves synaptic plasticity and long-term potentiation (LTP). These processes involve changes in the protein chemistry in different parts of the brain including the hippocampus which plays an important role in spatial cognition and memory. These processes are believed to be dependent on synthesis of new proteins which form the basis of memory. The protein synthesis underlying memory mechanism consolidation takes place in the hippocampus. Memory formation involves a number of signalling pathways associated with activation of many synaptic plasticity-related proteins, such as N-Methyl-D-Aspartic Acid (NMDA) Receptor, Ca2+/calmodulin-dependent protein kinase II (CaMKII), mitogen-activated protein kinases (MAPKs), glutamate dehydrogenases and many other proteins in the brain. This study was undertaken to investigate the role of the hippocampus in the formation of the spatial learning and memory in C57BL/6J mice undergoing spatial learning in the Morris Water Maze. The mice were sacrificed by cervical dislocation and the total protein in the hippocampus extracted and subjected to 2-dimenssional polyacrylamide gel electrophoresis. The proteins involved in the spatial learning process were identified and comparison was made between proteins expressed in the hippocampus of control and trained mice and also changes in the morphology of hippocampal dendritic arborisation were studid. The proteins were separated according to their isoelectric points and molecular weights. Twenty-six spots were chosen based upon ANOVA statistical analysis. The proteins expressed were analysed using LC/MS Mass Spectrometry. The study indicated high performance of learning in Morris water maze (MWM) and changes in the length and number of dendritic branches in cornu ammonis CA3 pyramidal cells and proteins identified in the mice which is known to be specially involved in, signal transduction and transport. In summary, using a proteomics approach, this study showed that spatial training affects network of proteins involved in energy metabolism and synaptic plasticity in the hippocampus, a brain region central to cognitive function. Further studies can help to identify the proteins and pathways of learning and memory mechanisms and changes of dendrite arborisation during spatial learning.